Effectiveness of Modern Teaching Methods; Evidence from Digital Learning Model of Modern Teaching Methods - Gul, Ejaz (Journal of Education and Vocational Research, 2016)
This paper elucidates the efficacy of three selected modern and innovative methods of learning by taking a group of 80 students of economics class at university level. Their opinion regarding three selected modern teaching methods was obtained through a questionnaire and statistical analysis of their opinion was carried out which indicated strong tendency towards mutual practice method as 40 out of 80 students (50%) declared it as very effective method of learning in the practice stage. On the other hand, 30 students (37.5%) opined that controlled practice method is moderately effective and 28 (35%) students opined that team practice method is slightly effective. After this analysis, students were put to practically learn use of econometric software ‘E Views’ through the same three selected methods. The digital model for their learning process was created using Computer Assisted Qualitative Data Assisted Software (CAQDAS). The statistical analysis of students’ opinion and digital analysis of practical learning process indicated that mutual practice is the most effective method of practice. It is because students learn better and fast when they are allowed to use their initiative and judgment. At the end, guidelines for effective teaching have been suggested.